The ‘private-collective’ innovation model under permissive licensing: a case study of OpenNebula open source software - Hmoud, Hazar Y. (2018)
This thesis aims for understanding how the ‘private-collective’ model of innovation works in permissive open source software. This model encourages the private investments in the collective software as well as the sharing of those investments with the collective community. By following this model in permissive open source software, this thesis suggested that private actors would experience a collective action problem referred to as a ‘business dilemma’. This dilemma is the difficult situation experienced by private actors who would be reaping rewards by sharing their private investments but also losing their competitive advantage because of free riders. Theoretically, private actors would be discouraged from sharing their private investments with the collective due to the business dilemma. However, in some real cases, we do not observe this constraint; private actors are not trapped by the business dilemma. Instead, they end up innovating and contributing to permissive open source software. As a result, this thesis would investigate and answer the research questions: ‘How can the private actors invest and share in permissive open source software without experiencing a business dilemma?’ and ‘Why private actors choose to invest and share rather than to free ride in permissive open source software?’ Ostrom’s theory of collective action is used as a lens for investigating the patterns of the private contributions and answering the research questions consequently. This theory suggests that people, even with the absence of formal regulations, can talk and share their local knowledge and experiences in order to collectively arrange the pattern of their actions and to extract themselves from collective action problems accordingly. OpenNebula open source software was the case study analysed. Findings are based upon an in-depth qualitative analysis of a substantial dataset involving 7,017 emails, 3,482 development requests, 4 technical OpenNebula official documentations and thousands of source code commits. Findings revealed that private actors are voluntary entering in an ‘active communications’ with other participants. Findings proposed that an ‘active communications’ act as a prerequisite for the active private contributions done by private actors. Those private contributions are locked within the collective software in the form of ‘collective complementarities’ through a ‘transformation process’. Several evidences proposed that this process worked to align the private interests of private actors with the collective interests of the software. Moreover, findings revealed that a set of ‘rules’ are emerged by the private actors and other participants in order to structure the ‘active communications’ and the ‘transformation process’. Several evidences proposed that these ‘rules’ worked to support the alignment between the private and the collective interests. Accordingly, it is proposed that the alignment between the private and the collective interests (which is done through the ‘active communications’, ‘transformation process’ and is supported through a set of ‘rules) encourages private actors to share and to link their private software with the collective. Without sharing, their private software would not be part of the ‘collective’ complementarities’ that are used in the different industries. This thesis makes novel contributions to the literature of open source. In particular, it extends the ‘private-collective’ model of innovation by introducing the ‘collective complementarities’ as a theoretical concept for locking the private benefit alongside with the collective one. It extends the open source literature by providing a better understanding of the collective software as a type of ‘commons’ that is exposed to private appropriation. In this way, it provides a set of arrangements that can bring the best of open source software that are sponsored by private actors. This thesis also encourages firms to: (1) share an ongoing control over the development of the software with the vibrant community members in order to develop software that can be used across industries and (2) harness information technology practices in their organizations to better serve the private and the collective interests.